Quality Control of Raw Plant Materials and Stability Testing under Accelerated Storage Conditions of Kheaw-Hom Remedy Extract - Sukkasem, Kanmanee; Itharat, Arunporn; Thongdeeying, Pakakrong; Pipatrattanaseree, Weerachai; Makchuchit, Sunita; Kongkwamcharoen, Chonticha; Davies, Neal M. (Asian Medical Journal and Alternative Medicine, 2024)
Introduction: Kheaw-Hom remedy (KH), a Thai traditional antipyretic medicine, is included in the National List of Essential Medicine. Currently, there is no scientific report on its standard requirements for quality control and stability testing. Objectives: To determine the quality control and stability testing of KH on anti-inflammatory activity and its bioactive marker Methods: Quality control methods (loss on drying, total ash, acid-insoluble ash, extractive values, and heavy metals) of KH and raw plant materials were performed according to Thai Herbal Pharmacopoeia (THP). The stability testing of the ethanolic extract of KH (KHE) was stored under 40 ± 2 ºC and 75 ± 5% relative humidity for 180 days. Anti-inflammatory activity on LPS-induced nitric oxide (NO) production in RAW264.7 macrophage cells were evaluated. Ethyl p-methoxycinnamate (EPMC), a bioactive marker, was analyzed using high performance liquid chromatography (HPLC). Results: KH showed loss on drying, total ash, acid-insoluble ash, ethanol soluble extractive and water-soluble extractive values of 8.66 ± 0.47%, 6.17 ± 0.06%, 1.14 ± 0.07%, 10.62 ± 0.12%, and 13.78 ± 0.54%, respectively. Eighteen plant materials met the requirements of THP. The anti-inflammatory activity on nitric oxide inhibition and EPMC content of KHE on day 180 exhibited no significant difference when compared with day 0. Conclusions: This study is the first report on quality control and stability testing of KH. All KH and its plant components conformed to the standard requirements of THP. KHE could be stored at room temperature for two years.